Resolving interactions between ion-cyclotron range of frequencies heating and the scrape-off layer plasma in EAST using divertor probes *This article is dedicated to the memory of Joel C Hosea. (7th March 2019) - Perkins, R J; Hosea, J C; Taylor, G; Bertelli, N; Kramer, G J; Luo, Z P; Qin, C M; Wang, L; Xu, J C; Zhang, X J
Abstract: Waves in the ion-cyclotron range of frequencies (ICRF) used for tokamak heating are known to interact strongly with the scrape-off layer (SOL) plasma, potentially limiting ICRF performance. We present the effect of ICRF heating on triple-probe signals in the Experimental Advanced Superconducting Tokamak (EAST) experiment, an advanced superconducting tokamak with two ICRF antennas and 12 MW of ICRF source power in support of high-power and long-pulse operation. Applying time-resolved magnetic mapping to the divertor probe arrays enables detailed sensing of the spatial structure of the SOL modifications. We observe a sharp transition in floating potential from negative to positive over a length scale of a centimeter at a major radius just inboard of the ICRF antenna. The largest changes in floating potential are observed not for probes connecting to the active ICRF antennas but rather to the main limiter or limiters for inactive lower hybrid launchers. Ion saturation current can be greatly reduced for probes mapping just in front of an antenna. Where relevant, comparison with results from the National Spherical Torus Experiment are made. This work will provide insight into sputtering, impurity production and antenna coupling as higher ICRF power levels are attempted on EAST.